Rasio Finansial Perusahaan dan Trade-Off Pelaporan Keuangan-Perpajakan - Toly, Agus Arianto; Fangie, Gloria; Maria, Machiko Giovanni (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
The research aims to determine the trade-off between the aggressiveness of financial reporting and taxation faced by management. By taking a sample of 230 company observations on the Indonesia Stock Exchange (BEI) for the 2019-2021 period using a purposive sampling method, this study analyzes the influence of five financial variables on the trade-off between financial reporting aggressiveness and taxation, including debt ratio, debt maturity, financing deficit. , internal and external capital market funding ratios, and profitability. The analysis used is multiple linear regression. The results of the research show that the level of debt ratios, long-term debt and financing deficits have a positive influence on the aggressiveness of financial reporting, while the funding ratio in the external capital market and profitability have a significant negative influence. This study provides guidance to auditors to carefully examine a company's financial statements to ensure compliance with accounting standards and fairness Keywords : Book-tax trade off; Financial ratio; Earnings management; Tax aggressiveness